2007
DOI: 10.1093/jn/137.9.2006
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Drosophila a Biotin-Deficient Diet for Multiple Generations Increases Stress Resistance and Lifespan and Alters Gene Expression and Histone Biotinylation Patterns3

Abstract: Energy restriction increases stress resistance and lifespan in Drosophila melanogaster and other species. The roles of individual nutrients in stress resistance and longevity are largely unknown. The vitamin biotin is a potential candidate for mediating these effects, given its known roles in stress signaling and gene regulation by epigenetic mechanisms, i.e. biotinylation of histones. Here, we tested the hypothesis that prolonged culture of Drosophila on biotin-deficient (BD) medium increases stress resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 33 publications
2
40
0
3
Order By: Relevance
“…After comparing the biotinylation levels of the same lysine residues (K9BioH3 and K18BioH3) with controls, Camporeale et al (2006) showed that reduced biotinylation in histones caused by knocking down a major catalytic enzyme (holocarboxylase synthetase, HCS) led to decreased lifespan and heat tolerance in treated flies compared to controls within one generation. In contrast, although Smith et al (2007) found that flies fed on a biotin-deficient diet for 12 generations also exhibited decreased biotinylated histones, their lifespan and resistance to heat stress actually increased relative to control lines. The divergent results in these two studies may imply that lifespan and heat stress resistance are impacted differently by short-term decreased histone biotinylation vs. adaptation to histone biotinylation deficiency over multiple generations.…”
Section: Within-generational Epigenetic Effectsmentioning
confidence: 75%
“…After comparing the biotinylation levels of the same lysine residues (K9BioH3 and K18BioH3) with controls, Camporeale et al (2006) showed that reduced biotinylation in histones caused by knocking down a major catalytic enzyme (holocarboxylase synthetase, HCS) led to decreased lifespan and heat tolerance in treated flies compared to controls within one generation. In contrast, although Smith et al (2007) found that flies fed on a biotin-deficient diet for 12 generations also exhibited decreased biotinylated histones, their lifespan and resistance to heat stress actually increased relative to control lines. The divergent results in these two studies may imply that lifespan and heat stress resistance are impacted differently by short-term decreased histone biotinylation vs. adaptation to histone biotinylation deficiency over multiple generations.…”
Section: Within-generational Epigenetic Effectsmentioning
confidence: 75%
“…Studies concerned with the impact of nutrition often assess the physiological and morphological responses of individuals exposed to different quality and amount of nutrients. These include studies of the impact of nutrition on body composition [4,5], stress tolerance [6,7], and reproduction and longevity [8 -11]. Less is known about the long-term/evolutionary consequences of transitions to different diets, although the potential interactions between 'historical' and 'present' diets will ultimately determine the fitness of the resulting phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting increased longevity and enhanced stress tolerance as a consequence of diet restriction or mild starvation as well as those showing increased inbreeding depression in some adult traits as a consequence of poor early nutrition demonstrate well how complex the role of nutrition in individual performance can be (e.g. Bubli et al 1998;Wenzel 2006;Burger et al 2007;Smith et al 2007;Valtonen et al 2011). Nevertheless, the effects of inbreeding on starvation resistance remain largely unexplored (Sverdlov and Wool 1975;Hoffmann et al 2001).…”
Section: Introductionmentioning
confidence: 99%